How successful teachers see their role and work in schools with poor cultures of teaching and learning - Masanabo, Nontokozo Precious (My University, 2020)
In education by far, the only way managerialism can tell whether the teachers are successful is through marks and results from high stakes testing. And at the moment, that is the only measure of testing teachers’ successes in their work that exists. This study was conducted on the premise that there is more to teachers' work and roles for it to only be measured as successful, by the testing results of learners alone. In South Africa, it is a widely held belief that matric results are an indicator of the schools’ functionality. On the contrary, the assumption that matric results suggest that a school has a healthy culture of teaching and learning, does not recognize the nature of work that successful teaches do in the difficult climates in which they work. Available research on schooling in many South African township schools reports on numerous challenges faced by schools and how school leaders struggle to maintain a positive culture of teaching and learning amid issues such as school violence, drug abuse, managerial issues, school politics, etc. With this said, the teachers involved in this study are still recognized as successful teachers in their schools, districts, and even provinces. This study was conducted to understand how successful teachers understand their role and work in schools with poor cultures of learning and teaching. This study involved four teachers from two Sowetan schools. The data was collected through semi-structured interviews to understand teachers’ experiences of working in schools with a poor culture of teaching and learning. It explored how they continue to promote effective cultures of learning and teaching in their classrooms. This study found that teacher agency and the teacher’s ability to engage in some sort of emotional labour created opportunities for teachers to create relationships with their learners that enables them to work despite the threatening nature of their work environment and organizational culture. These relationships negatively impacted on by the class sizes, and the resources available for the teachers and the learners to be able to carry out their duties successfully.
A report submitted n fulfilment of the requirements of the degree of Master of Education to the Wits School of Education, Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2020